092 Motor neuron disease with malignancy: clinical and pathophysiological insights. (29th July 2019) - Higashihara, Mana; Menon, Parvathi; Geevasinga, Nimeshan; Bos, Mehdi AJVan den; Kiernan, Matthew C; Vucic, Steve
Abstract : Introduction: While some regard an association between motor neuron disease (MND) and malignancy as co-incidental, others have argued that it could represent a distinct clinical entity. The present study undertook in depth phenotyping along with assessment of cortical function to further explore disease pathophysiology in MND with malignancy (MND-M) patients. Methods: Clinical features along with assessment of peripheral and cortical function was undertaken in 13 MND-M and results were compared to sporadic and familial MND cohorts. Results: From a cohort 13 patients (10 males; aged 65.2±2.0 years), 30.8% were diagnosed with a haematological malignancy. The lower motor neuron phenotype predominated in the in the MND-M patients (χ2=10.8, P<0.01), with the upper motor neuron (UMN) score being significantly reduced in MND-M patients compared to sporadic and familial MND cohorts (χ2=6.84, P<0.01). The neurological deficits did not respond to treatment of the underlying malignancy in the majority of MND-M (92%) patients, and as such there were no significant differences in survival between the cohorts. Despite a paucity of UMN signs, cortical hyperexcitability was evident in MND-M patients, as indicated by reduction in short interval intracortical inhibition (P<0.01) and increase in motor evoked potential amplitude (P<0.01), that were similar to findings in sporadic and familial MND cohorts. Conclusions: The present study suggests that MND-M falls within the spectrum of MND. A co-incidental association between MND and malignancy is underscored by cortical dysfunction and clinical findings which seems within the spectrum of abnormality evident in classical MND phenotypes.